(untitled) (Training and Practice : Journal of Educational Sciences, 2018)
In education training can be found as a practise oriented form of teaching. But there is a question how training can be the most efficient in business education. Of course, it helps to develop capabilities and competences, but it is not sure whether the main goal, that the knowledge is integrated at the interpretation level of the students, is achieved. On the other hand, the leaders, managers (low and middle level as well), especially the HR workers at companies, used to need to train their employees. In the last two years we started to apply a special way of training, in which the students take apart in a training and prepare an own program as well. It is called Sample Training Method (STM) which gives a chance to the students to get some experience of group leading and they can develop themselves.